COMBINATIONS OF WHARTON JELLY DERIVED EXOSOMES AND SALICYLIC ACID: A NEW HOPE FOR ERADICATION OF CUTANEOUS LEISHMANIASIS - Koken, Gulnaz Yildirim; Abamor, Emrah Sefik; Allahverdiyev, Adil; Karaoz, Erdal (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2022)
The aim of the current study is to obtain wharton jelly derived exosomes, prepare therapeutic formulations including combinations of isolated exosomes and salicylic acid, investigate their in vitro antileishmanial activities against L.major promastigotes and amastigotes in order to develop a new alternative approach for recovery of Cutaneous Leishmaniasis. Exosomes isolated from mesenchymal stem cells were characterized by flow cytomeric analysis, zeta-sizer measurements and SEM visualization techniques. Following to demonstration of exosome existence, non-toxic concentrations of exosomes and salicylic acid were determined on L929 and J774 cells. The combined doses of exosomes and salicylic acid were applied on L.major promastigote and amastigote-macrophage culture by evaluation of various biological parameters of parasites such as viability, metabolic activity and infectivity. Obtained results indicate that combinations including non-toxic concentrations of exosome and salicylic acid displayed brilliant antileishmanial performances against each form of Leishmania parasites and this effect was too much bigger than use of these agents alone. We observed that combination applications substantially inhibited the viability and metabolic activity values of parasites and completely prevent the infection of macrophages with Leishmania promastigotes. These results reveal that exosome and salicylic acid combinations possessed significant inhibitory efficacies on L.major parasites. We foreseen that they would be further used in eradication of Cutaneous Leishmaniasis with a high success.
Keywords: Leishmaniasis; extracellular vesicles; exosome; mesenchymal stem cell; Wharton Jelly; salicylic acid; MESENCHYMAL STEM-CELLS; UMBILICAL-CORD; GENE-EXPRESSION; TELOMERASE; ANGIOGENESIS; Environmental Sciences & Ecology